Persepsi Masyarakat terhadap Tradisi Nglangkahi Kakak dalam Perkawinan: Studi Kasus Desa Kayangan Kecamatan Diwek Kabupaten Jombang - Hilwatun Nisa; Abdullah Afif (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
This study examines the public perception of the nglangkahi kakak tradition in marriage in Kayangan Village, Diwek District, Jombang Regency. The study employs a qualitative approach with a focus on sociology. Observation, interviews, and direct field documentation were used as methods to collect data. The research also analyzes literature from legal documents and academic journals. The findings show that there is a diversity of perceptions among the community regarding this tradition. Some community members still strongly adhere to the tradition due to customary, ethical, and familial harmony reasons, while others have started to disregard it based on rational considerations such as age, mental readiness, and economic factors. Thus, the nglangkahi kakak tradition in Kayangan Village is undergoing change in line with social development and the modern values adopted by the local community.